Compound heterozygous ZP1 mutations cause empty follicle syndrome in infertile sisters. Issue 11 (29th July 2019) - Sun, Ling; Fang, Xiang; Chen, Zhiheng; Zhang, Hanwang; Zhang, Zhan; Zhou, Pei; Xue, Ting; Peng, Xiaofang; Zhu, Qianying; Yin, Minna; Liu, Chunlin; Deng, Yu; et al.
Abstract: Empty follicle syndrome (EFS) is a condition in which no oocyte is retrieved from mature follicles after proper ovarian stimulation in an in vitro fertilization procedure. Genetic evidence accumulates for the etiology of recurrent EFS without pharmacological or iatrogenic problems. In this study, we present two infertile sisters in a family with EFS after three cycles of standard ovarian stimulation with human chorionic gonadotrophin and/or gonadotropin‐releasing hormone agonist therapy. Via whole‐exome sequencing and cosegregation test, we identified compound heterozygous mutations in the gene of ZP1 in both of the infertile sisters. Coimmunoprecipitation tests and homology modeling analysis confirmed that both mutated ZP1 disrupt the formation of oocyte zona pellucida by interrupting the interaction among ZP1, ZP2, and ZP3. We thus propose that the specific mutations in ZP1 gene render a causality for the intractable EFS.